A note on the international coordination of antidoping policies - Emrich, E.; Pierdzioch, C. (Journal of Sports Economics, 2015)
We apply ideas put forward in the literature on the international coordination of macroeconomic and trade policies to study the merits of an international coordination of antidoping policies. Without international coordination of antidoping policies, sports associations and National Antidoping Agencies that comply with an international regulatory framework like the World Antidoping Code are at a disadvantage. We sketch a simple game-theoretic model to illustrate this disadvantage, and the advantage of an international coordination of antidoping policies. Finally, we address the limitations of our model and how it could be extended in future research.